PERANAN KEPALA SEKOLAH DALAM MANAJEMEN PENINGKATAN MUTU PEMBELAJARAN (Studi Kasus di SDN Kabupaten Semarang) - Yuyarti Yuyarti (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2009)
Education paradigm gives a wide competence to school in developing their potentials. In increasing capabilities from various aspects of its managerials in order to reach their aims adjust to visions and missions. School success is headmaster’s success. Headmaster are they who knows a lot of about duty and decides goodnesses for their school. In other side, headmaster is also as a formal official, he is a manager, leader, teacher, all act as a staff in framework of applicating the school quality and management of teaching and learning quality at once. According to this backgrounda above, researcher chose elementary school in Semarang Regency because the elementary school has special qualities. Methode which is used in this research is qualitative methode, by collecting indication or information from yield of observation, interviews, and documents about the roles of headmasters as a planner, organizer, motivator, and supervisor of the increasement of teaching and learning quality. The research resulted that, headmaster has made teaching and learning plan well, such as: annually program, semester program, evaluation, means and instruments, and creating a condusive climate. His roles as an organizer resulted involvement of parents, completing means and instrumens, monitoring teaching and learning process, forming a committee stucture to attend various of competition. The role of headmaster as a motivator, such as: building “long life education” spirit, scolarly paper production, good-achieving teachers prosperity upgrading, making Teachers Work Group (KKG) effective. His role as a supervisor, which was got from the research results of three state elementary school, is by supervision to all planning, organizing, activation, and evaluation to the making of Teaching and Learning Realization Planning examples in teaching and learning activities, directly or indirectly, all evaluation is done periodically. Conclution of the research about the role of headmaster in increasing teaching and learning quality in state elementary school in Semarang Regency has applied the functions of management well and been planned. It has been proven that some of teacher had passed Undergraduate Program, attended seminars and trainings so often, fulfillment of means and instruments, and many other achievements in academic or non academic.